1999
DOI: 10.1007/pl00012336
|View full text |Cite
|
Sign up to set email alerts
|

Total Esophagectomy versus Proximal Esophagectomy for Esophageal Cancer at the Cervicothoracic Junction

Abstract: To investigate the adequate extent of esophagectomy and lymphadenectomy for an esophageal cancer localized at the cervicothoracic junction, the mortality and morbidity rates, survival rates, and patterns of recurrence were retrospectively analyzed in two groups-14 patients who underwent total esophagectomy with or without laryngectomy and 15 patients who underwent proximal esophagectomy with or without laryngectomy-at Kurume University Hospital from 1981 to 1996. Proximal esophagectomy with or without laryngec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 7 publications
2
9
0
4
Order By: Relevance
“…Five of these patients had metastasis to mediastinal lymph nodes (M1-Lym) and 10 patients had extracapsular invasion, both of which decreased the possibility of long-term survival. Our results are consistent with those of previous studies that found that the pattern of recurrence after surgical resection is more often locoregional than distant metastasis [16,17].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Five of these patients had metastasis to mediastinal lymph nodes (M1-Lym) and 10 patients had extracapsular invasion, both of which decreased the possibility of long-term survival. Our results are consistent with those of previous studies that found that the pattern of recurrence after surgical resection is more often locoregional than distant metastasis [16,17].…”
Section: Discussionsupporting
confidence: 95%
“…Prognostic factors reported by previous studies to influence the long-term survival of patients with hypopharyngeal and cervical esophageal carcinoma include positive surgical margins [8,15], lymph node involvement [8,16], postoperative complications [6,17], patient gender [6,17], depth of tumor invasion [2,6,16], intramural metastasis [6], and tumor size more than 5 cm [18]. However, most of these studies combined results from cases of hypopharyngeal and cervical esophageal carcinoma or from cases treated with chemotherapy or radiotherapy without surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In detail, survival among patients with curative segmental esophagectomy was significantly better than after total resection (p ¼ 0.017) [48]. That may be explained by lower hospital mortality rates as confirmed by our meta-analysis (Tables 1-3).…”
Section: Postoperative Outcome and Survivalsupporting
confidence: 59%
“…The extent of esophagectomy did not influence overall survival [48]. In detail, survival among patients with curative segmental esophagectomy was significantly better than after total resection (p ¼ 0.017) [48].…”
Section: Postoperative Outcome and Survivalmentioning
confidence: 98%
“…On the other hand, thoracic surgeons adopt subtotal esophagectomy or total esophagectomy with laryngectomy followed by esophageal reconstruction using a gastric pedicle because of a high incidence of invasion into the thoracic esophagus or a high incidence of multiple primary cancers in the thoracic esophagus. They think of lymphadenectomy for cancer of the cervical esophagus as similar to that for cancer of the upper thoracic esophagus [6]. Recently, a less invasive procedure for cervical esophagectomy, without laryngectomy, has been introduced for cancer of the cervical esophagus with respect to achieving a better quality of postoperative life [7].…”
Section: Introductionmentioning
confidence: 99%